Range research highlights - E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1985)
A 1135 acre tract of native bluestem pasture 5 miles northeast of Manhattan was acquired by the Kansas Agricultural Experiment Station in 1946 for range research. Professor A.G. Picket was in charge of the beef cattle research at that time. Professor Kling Anderson of the Department of Agronomy cooperated with the Department of Animal Husbandry in collecting grazing research data. Professor Clenton Owensby, presently assisted by Mr. Gene Towne, took over Dr. Anderson's responsibilities after his retirement. Mr. Jim Whitney is responsible for supervising work at the unit. Many students, staff, faculty, and producers have aided in many aspects of the studies. Following are summaries of several of the research projects that have been carried out at the Range Research Center.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Rangeland; Bluestem